1996
DOI: 10.1055/s-2007-979535
|View full text |Cite
|
Sign up to set email alerts
|

The Revised Monoamine Theory of Depression: A Modulatory Role for Monoamines, Based on New Findings From Monoamine Depletion Experiments in Humans

Abstract: The original hypothesis that brain monoamine systems have a primary direct role in depression has been through several modifications during the past 30 years. In order to test this hypothesis and more fully characterize the role of serotonin and catecholamines in the pathophysiology of depression and the mechanism of action of antidepressant treatments, our research group has conducted a series of studies evaluating monoamine depletion induced brief clinical relapse following different types of antidepressant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
161
0
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(174 citation statements)
references
References 18 publications
6
161
0
7
Order By: Relevance
“…It is generally assumed that dysfunctional monoaminergic transmission may underlie various symptoms of depression, including the susceptibility to stress (see Heninger et al, 1996;Mongeau et al, 1997;Holsboer, 2001;Morilak and Frazer, 2004). Since galanin and the galanin receptors are expressed in both the NA and 5-HT systems, it is possible that the role of galanin in depression-like behavior may, at least partially, be related to modulation of brain NA and/or 5-HT functions at the cell body level and/or their projection areas.…”
Section: Integrative Mechanism Of Galanininergic Regulation Of Depresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally assumed that dysfunctional monoaminergic transmission may underlie various symptoms of depression, including the susceptibility to stress (see Heninger et al, 1996;Mongeau et al, 1997;Holsboer, 2001;Morilak and Frazer, 2004). Since galanin and the galanin receptors are expressed in both the NA and 5-HT systems, it is possible that the role of galanin in depression-like behavior may, at least partially, be related to modulation of brain NA and/or 5-HT functions at the cell body level and/or their projection areas.…”
Section: Integrative Mechanism Of Galanininergic Regulation Of Depresmentioning
confidence: 99%
“…Dysfunctions of brain noradrenaline (NA) and serotonin (5-hydroxytryptamine, 5-HT) neurotransmission as a consequence of uncontrollable (chronic) stress are implicated in depression (see Weiss et al, 1981;Heninger et al, 1996;Holsboer, 2001). In fact, the current pharmacotherapy of depression is also mainly based on use of compounds correcting dysfunctions in monoaminergic transmission, including selective serotonin reuptake inhibitors (SSRIs) (see Frazer, 1997;Millan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In an interesting parallel in humans, depressed patients treated with serotonin reuptake inhibitors are prone to relapse if serotonin levels are pharmacologically depleted, but not if catecholamines are depleted. Conversely, catecholamine, but not serotonin, depletion produces relapse in patients that have been treated with norepinephrine reuptake inhibitors (Delgado et al 1990(Delgado et al , 1991Heninger et al 1996). On the basis of such findings, some authors have suggested that antidepressants that have varying affinity for noradrenergic versus serotonergic systems produce their behavioral effects via separate mechanisms (Page et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Delgado and co-workers have suggested that although both NE and serotonin (5-HT) mediate antidepressant responses, these actions are independent, that is, the depletion of one neurotransmitter had little effect on patients treated with an AD acting primarily on the other neurotransmitter (Delgado and Moreno, 2000;Heninger et al, 1996). Therefore, it was interesting to use the recently generated (Xu et al, 2000), genetically modified mice lacking the NET (NET À/À mice) for studying the role of the NET and the noradrenergic system in the actions of ADs, and to compare the effects of ADs with those described in previous studies carried out with mice lacking the 5-HT transporter (Holmes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%